Viscosity to entropy density ratio (η/s) in nanoliquid. (3rd September 2022) - Islam, Md Moinul; De, Alokkumar; Pandit, Deepak; Dey, Balaram; Sakib, Nazmus; Bhattacharya, Srijit
ABSTRACT: We present the coefficient of viscosity ( η ), entropy (S) and viscosity to entropy density (s) ratio ( η / s ) for aqueous silver nanoparticle (AgNP) solution at temperatures T = 273–300 K performing experiments and examining the same with discrete dipole approximation (DDA) simulation. The experimental UV-Visible dipole extinction spectra of the nanoliquid, matched with simulations, explore cluster morphologies. The latter is used for the calculation of η (cluster volume fraction 4–10%; NP, cluster radii 8–15 nm and 35–55 nm, respectively). In addition, dimer (AgNP-AgNP) formation free energy and S are explored at those T's. We determine η / s ratio exploiting nanoparticle behaviour. The value of η / s is found lower than that of water and similar to strongly correlated liquid He 4, owing to higher S for NP agglomeration. Our results of η, S and η / s are also corroborated from hard sphere model calculation. This, to the best of our knowledge, is the first attempt to determine η / s in NP.